Computational mechanics of multiphase materials – modeling strategies at different scales - Meschke, Günther; Leonhart, Dirk; Timothy, Jithender J.; Zhou, Meng-Meng (Computer Assisted Methods in Engineering and Science, 2017)
The paper addresses various scale-bridging modeling and discretization strategies for multiphase porous materials, starting with a micromechanics model for ion transport within the pore space to generate homogenized diffusion coefficients. Using homogenized macroscopic properties, the theory of poromechanics provides the modeling framework for the macroscopic representation of transport and phase change processes as it is demonstrated for freezing of porous materials using a three-field formulation. The theory of poromechanics is again employed as an appropriate representation of more or less intact porous materials, in conjunction with a two-field Extended Finite Element model as a scale bridging tool to describe coupled hydro-mechanical processes in cracked porous materials at a macroscopic level.